(untitled) - Brian Tierney (New York, 1982)
The book presents the history of the early period from A.D. 300 to A.D. 1475, It describes the feudal politics, feudal welfare, and feudal society, church history, law, political theory, philosophy, art, and literature. All the material has been arraged to bring out more clearly the chronological structure of medieval history. The central themes is the emergence of a distinctively Western civilization in medieval Europe, and the book gives the clearest possible account of this complex phenomena
Keywords: middle-ages history